Device‐measured physical activity and its association with physical function in adults with type 2 diabetes mellitus. Issue 6 (25th September 2020) - Mickute, M.; Henson, J.; Rowlands, A. V.; Sargeant, J. A.; Webb, D.; Hall, A. P.; Edwardson, C. L.; Baldry, E. L.; Brady, E. M.; Khunti, K.; Davies, M. J.; Yates, T.
Abstract: Aim: To quantify how differences in metrics characterizing physical activity and sedentary behaviour in type 2 diabetes are associated with physical function. Methods: This analysis included participants' data from the Chronotype of Patients with Type 2 Diabetes and Effect on Glycaemic Control (CODEC) cross‐sectional study. Data were stratified into two groups according to their short physical performance battery (SPPB) score (impaired physical function = SPPB < 10 and normal physical function = SPPB ≥ 10). Hand‐grip strength, sit‐to‐stand 60 (STS‐60) and the Duke Activity Status Index (DASI) score were used to assess functional capacity, while physical activity metrics were measured with a wrist‐worn accelerometer. The associations between physical activity metrics and measures of functional capacity were analysed using generalized linear modelling. Results: Some 635 adults (median age 66 years, 34% female) were included in this analysis. Overall, 29% of the cohort scored < 10 in the SPPB test indicating impaired physical function. This group spent more time in prolonged sedentary behaviour (600.7 vs. 572.5 min) and undertook less‐intense physical activity. Each sd increase in physical activity volume and intensity gradients for those with impaired physical function was associated with 17% more repetitions for STS‐60 with similar associations seen for DASI score. Each sd in sedentary time was associated with 15% fewer repetitions in STS‐60 and 16% lower DASI score in those with impaired physical function, whereas in normal physical function group it was 2% and 1%, respectively. Conclusions: The strength of the associations for physical activity measures and functional capacity were modified by physical function status, with the strongest association seen in those with impaired physical function.